To Meat or Not To Meat: Proton Nuclear Magnetic Resonance Analysis of the lipid composition of novel plant-based meat alternatives in the Finnish market - Wadiyo, Samantha (My University, 2023)
Novel plant-based meat alternatives are a group of products based on plant sources of protein including soy, peas, oats, and a variety of beans and cereals, developed to mimic the appearance, texture, and sensory attributes to meat. This study studied the lipid profiles of 178 samples, including novel plant-based meat alternatives and animal meat sourced products available in the Finnish market. The products included 15 plant-based protein sources (legumes, cereals, seeds), 4 animal-based protein sources, categorized into 11 product types. Polar lipids were extracted from the samples and analyzed with 1H nuclear magnetic resonance spectroscopy. An untargeted/targeted multivariate model was applied to the results using principal component analysis (PCA). Lipids were detected in all the samples analyzed, with the highest lipid composition in products processed from oats, peas, chickpeas, soy and fava beans, high saturated fat in animal-based products, with high omega-3 FAs and PUFAs in salmon products. Additionally, a correlation between the extent of food processing and the lipid composition was observed.
Keywords: Novel plant-based meat alternatives, lipid composition, 1H NMR spectroscopy, metabolomics, food processing